Home grocery listing hardware system and mobile application with speech recognition feature - Mohamad Faris Eizlan Suhaimi; Aiman Zakwan Jidin; Haslinah Mohd Nasir; Mohd Haidar Md Hamzah; Mohd Syafiq Mispan (Institute of Advanced Engineering and Science, 2026)
A home grocery list is a crucial aspect of household management that ensures sufficient kitchen supplies. The classic pen-and-paper grocery list is ineffective since it is time-consuming and prone to human error. Therefore, in this study, we proposed a microcontroller-based home grocery listing system using a barcode scanner and speech recognition. The proposed system consists of hardware and a mobile application. The main hardware components are the ESP32-S3 microcontroller, MH-ET barcode scanner v3.0, 20×4 LCD, and 2.4 GHz wireless keyboard. The mobile application is developed using the MIT App Inventor. Through the hardware, the system receives user input from barcode scanning or manual data entry using the keyboard. The data captured using a barcode scanner or keyboard is stored in the memory. Subsequently, the data is transmitted to the mobile application of the home grocery listing system via WiFi. Moreover, the mobile application is also equipped with user input via speech recognition and manual data entry using the keyboard. Hence, users have the flexibility to input the grocery list using four methods within the system. The developed home grocery listing system gives a new, satisfying experience to the users and a convenient way for them to make a home grocery list.